2023
DOI: 10.1111/jnc.15755
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐restrictive silencer factor/repressor element 1‐silencing transcription factor (NRSF/REST) controls spatial K+ buffering in primary cortical astrocytes

Abstract: Neuron‐restrictive silencer factor/repressor element 1 (RE1)‐silencing transcription factor (NRSF/REST) is a transcriptional repressor of a large cluster of neural genes containing RE1 motifs in their promoter region. NRSF/REST is ubiquitously expressed in non‐neuronal cells, including astrocytes, while it is down‐regulated during neuronal differentiation. While neuronal NRSF/REST homeostatically regulates intrinsic excitability and synaptic transmission, the role of the high NRSF/REST expression levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 95 publications
(168 reference statements)
1
7
0
Order By: Relevance
“…Moreover, it has been recently demonstrated that REST increases the strength of axo‐somatic inhibitory synapses onto excitatory neurons, while having no effect when the postsynaptic target cell was another inhibitory neuron 13 . A similar homeostatic effect was recently observed in astrocytes, where REST increases the transcription of the glutamate transporter GLT1 and favors the membrane exposure of the potassium channel Kir4.1, thus increasing glutamate and potassium clearance from the synaptic environment 14 …”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Moreover, it has been recently demonstrated that REST increases the strength of axo‐somatic inhibitory synapses onto excitatory neurons, while having no effect when the postsynaptic target cell was another inhibitory neuron 13 . A similar homeostatic effect was recently observed in astrocytes, where REST increases the transcription of the glutamate transporter GLT1 and favors the membrane exposure of the potassium channel Kir4.1, thus increasing glutamate and potassium clearance from the synaptic environment 14 …”
Section: Introductionmentioning
confidence: 59%
“…REST has been shown to play different roles under physiological conditions or under conditions of pathological hyperexcitability, ranging from homeostatic to pro‐epileptogenic effects 13,14,26,29,30 . However, a clear picture is still largely missing 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that REST KO primary astrocytes increase neuronal excitability by decreasing K + buffering and synaptic glutamate uptake. 56 In this context, the observed transcriptional increase of astrocyte Connexin-30, which during development contributes to the closure of the plasticity window, could represent a homeostatic mechanism during a phase of enhanced plasticity in adult life. It will be interesting to evaluate whether the plasticizing effects of REST downregulation occur, at least in part, through these mechanisms or whether there are different pathways leading to the reinstatement of V1 plasticity.…”
Section: Discussionmentioning
confidence: 99%